Associated factors influencing in publications produced by professors in San Marcos University - 2010 - Mendoza Arana, Pedro Jesús (2012)
A qualitative study designed for identifying factors influencing in publications produced by professors in San Marcos University Medical School. The researchers performed semi-structured interviews in a group of professors of the aforementioned school identified as significantly producing research and review papers. These persons were identified using the 2010 Database of the Research Council in San Marcos University. We identified the following factors facilitating publications: liaisons with foreign institutions outside Peru, discipline, training, focusing, multidisciplinary interactions, team building; and blocking factors identified were as follows: academic load and lack of resources for editorial activities. In a second level for analysis, we concluded that these are the circumstances reinforcing facilitating factors: participation in research networks and specialization in research activities. We also identified circumstances reinforcing blocking factors: research activities are highly concentrated and marginally positioned.